STRATEGIC PLAN FORMULATION PROCESS IN PUBLIC SERVICE ORGANISATIONS IN THE GAMBIA - Banna , SAWANEH (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
The paper examined formal strategic plan formulation process, application of strategic analysis tools, and assessment of managerial and stakeholders’ involvement in public service organisations (PSOs) in The Gambia. The study adopted “cross-sectional survey design”, through the administration of structured questionnaire of five-point Likert scale among the selected PSOs, with a sample size of 211 senior public servants, using probability-proportionate-to-size sampling technique from the study population (1058). Data collected were analysed using descriptive statistics techniques such as frequencies, percentages, means and standard deviations with the help of SPSS software version 20. The results showed that, in the process of formulating formal strategic plans, PSOs determined their missions and visions, developed long-term objectives, assessed both internal and external environments, and generated and evaluated strategic choices. Equally, the findings indicated that PSOs made commitments to their strategic plans, did both internal and external validation of the strategic plans, and formulated strategic plans to accommodate the interests of diverse groups and individuals. The paper concluded that PSOs in The Gambia followed formalised strategy formulation process in developing their strategic plans with key elements included.